Peran Arsiparis dalam Meningkatkan Akuntabilitas dan Transparansi Persuratan di Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Provinsi Bali - Cindy Sidabutar; I Kadek Rian Prayana (MASALIQ, 2026)
This study is grounded in the importance of archives as legal and administrative instruments that safeguard the integrity of governmental processes, as well as in the challenges of archival digitization that demand archivists’ professionalism, particularly in state audit institutions such as the Audit Board of the Republic of Indonesia (BPK RI). The study aimed to analyze the role of archivists in enhancing accountability and transparency in correspondence management at BPK RI Representative Office of Bali Province. Using a descriptive qualitative method through interviews, observations, and document studies, this research examined the implementation of regulation-based archival and correspondence management, particularly through the use of the JASMIN application, Tata Naskah Dinas, Kode Klasifikasi Arsip, and Jadwal Retensi Arsip. The findings showed that archivists hold a strategic role as controllers of correspondence flows, guardians of audit document integrity, and mediators between public information disclosure and the protection of sensitive data. Digitization through JASMIN strengthened document traceability and security; however, the limited number of archivists remains a major obstacle to consistent archival management in each work unit. The study recommends increasing archivist human resources, providing continuous training, and strengthening inter-unit coordination as strategic measures to achieve more accountable, transparent, and sustainable archival governance within BPK RI Representative Office of Bali Province.